A Case for the Young Foucault. Issue 3 (2nd October 2022) - Behrent, Michael C.
ABSTRACT: Between 1949 and 1961 (or, arguably, 1966), three interconnected dimensions of Foucault's early thought emerged. First, the young Foucault offered a Hegelian perspective on Kant's notion of the transcendental. The a priori conditions of thought, Foucault suggested, both shape and arise from historical experience. Second, Foucault drew on Heidegger's study of Kant to argue that modern thought rests on the premise of human finitude and embraces a problematic epistemology rooted in philosophical anthropology. Foucault argued that anthropology enabled a vast extension of the scope of possible knowledge predicated on the falsely modest pretense that human understanding is inherently limited, even as it embraced a diminished conception of human existence. Third, Foucault developed a pointed critique of contemporary psychology and psychiatry, maintaining that they fallaciously seek to acquire positive knowledge of human beings, despite the fact the latter are inherently defined by what Foucault called "negativity." This three-pronged interpretation of the young Foucault allows us to better situate Foucault's work in intellectual history, to clarify his key arguments, and to grasp the articulation of his youthful and his mature thought.